The Insights on Why Diabetes Prevalence May Increase Amid or Post COVID-19 Pandemic - Sibiya, Ntethelelo; Mzimela, Nomusa; Mbatha, Bonisiwe; Ngubane, Phikelelani; Khathi, Andile (Current Diabetes Reviews, 2023)
Background: Diabetes mellitus and prediabetes have been shown to be associated with high rates of developing severe COVID 19 complications resulting in morbidity and mortality. Emerging reports suggest that COVID 19 is associated with glycaemic control aberrations, although the extent is not clear at present. Accordingly, in this review, the efforts are directed to shed light on why we can anticipate an increase in diabetes cases amid or post-COVID 19 pandemic. Methods: Articles reviewed were identified using the Google Scholar database, and the search was done using the English language. Results: Previous studies have shown that viral inflammation triggers insulin resistance, which can progress to overt diabetes. SARS-CoV-2 has also been shown to cause acute pancreatitis, which can increase the risk of developing diabetes mellitus. The control of the COVID 19 pandemic partly relied on non-pharmaceutical measures, which included lockdowns. This resulted in a lack of physical activity and unhealthy eating behaviour, which could contribute to obesity and, ultimately, insulin resistance. Conclusion: While no concrete data has been established on the possibility of seeing an increase in diabetes prevalence due to COVID 19, studies are necessary to establish the link. Despite the unavailability of data at present, we suggest that frequent screening of diabetes and prediabetes should be encouraged, especially in those individuals with a history of COVID 19 infection.
Keywords: insulin resistance